Personal computer versus personal computer/mobile device combination users' preclinical laboratory e‐learning activity. Issue 4 (15th November 2016) - Kon, Haruka; Kobayashi, Hiroshi; Sakurai, Naoki; Watanabe, Kiyoshi; Yamaga, Yoshiro; Ono, Takahiro
Abstract: Aim: The aim of the present study was to clarify differences between personal computer (PC)/mobile device combination and PC‐only user patterns. We analyzed access frequency and time spent on a complete denture preclinical website in order to maximize website effectiveness. Methods: Fourth‐year undergraduate students (N=41) in the preclinical complete denture laboratory course were invited to participate in this survey during the final week of the course to track login data. Students accessed video demonstrations and quizzes via our e‐learning site/course program, and were instructed to view online demonstrations before classes. When the course concluded, participating students filled out a questionnaire about the program, their opinions, and devices they had used to access the site. Results: Combination user access was significantly more frequent than PC‐only during supplementary learning time, indicating that students with mobile devices studied during lunch breaks and before morning classes. Most students had favorable opinions of the e‐learning site, but a few combination users commented that some videos were too long and that descriptive answers were difficult on smartphones. Conclusions: These results imply that mobile devices' increased accessibility encouraged learning by enabling more efficient time use between classes. They also suggest that e‐learning system improvements should cater to mobile device users by reducing video length and including more short‐answer questions.